2021
DOI: 10.2174/1573406415666191107121757
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Antimicrobial Evaluation and Docking Study of Novel 3,5-Disubstituted-2-Isoxazoline and 1,3,5-Trisubstituted-2-Pyrazoline Derivatives

Abstract: Background: The frequent use of antibacterial agents is leading to antimicrobial resistance, which is one of the biggest threats to global health today. Therefore, the discovery of novel antimicrobial agents is still urgently needed to overcome the severe infections caused by these putative pathogens resistant to currently available drugs. Objective: The present work was aimed to synthesize and investigate the preliminary structure-activity relationships (SARs) of isoxazoline and pyrazoline derivatives as an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…The molecular docking studies of 55 and 56 to GlcN-6-P synthase (pdbid: 1moq) showed that obtained inhibitors may bind to the ISOM active site via interactions with Ala602, Ser349 and Thr302 residues. Estimated values of K i for 55 and 56 were 0.769 and 4.21 µM and their binding energies were −8.34 and −7.33 kcal/mol, respectively 73 .…”
Section: Heterocyclic Inhibitors Targeting the Active Sites Of Glcn-6...mentioning
confidence: 97%
See 2 more Smart Citations
“…The molecular docking studies of 55 and 56 to GlcN-6-P synthase (pdbid: 1moq) showed that obtained inhibitors may bind to the ISOM active site via interactions with Ala602, Ser349 and Thr302 residues. Estimated values of K i for 55 and 56 were 0.769 and 4.21 µM and their binding energies were −8.34 and −7.33 kcal/mol, respectively 73 .…”
Section: Heterocyclic Inhibitors Targeting the Active Sites Of Glcn-6...mentioning
confidence: 97%
“…Ismail and co-workers 73 characterised a series of 1,2-diazole- and 1,2-oxazole-based compounds as potential antimicrobial agents. The synthesis of inhibitors was a two-step procedure, in which p- hydroxy acetophenone was condensed in an aldol manner with 3,3-dimethoxybenzaldehyde or thiophene-2-carbaldehyde, resulting in chalcones 53 and 54 .…”
Section: Heterocyclic Inhibitors Targeting the Active Sites Of Glcn-6...mentioning
confidence: 99%
See 1 more Smart Citation
“…The synthesized chalcone derivatives ( 1 a – d ) were treated with hydrazine hydrate to obtain pyrazolines ( 2 a – c ). The formed pyrazolines ( 2 a – c ) were further reacted with methyl chloroformate and choloroacetyl chloride to prepare the modified pyrazoline derivatives ( 3 a – b ) and ( 4 a – b ) [46] . (Scheme 3)…”
Section: Chemistry Of Chalcone Derived Pyrazoline Derivativesmentioning
confidence: 99%
“…The compound 4‐(5‐Thiophen‐2‐yl)‐4,5‐dihydro‐1H‐pyrazol‐3‐yl) phenol ( 2 c ) was found to possess more potent activity in a concentration ranging from as low as 10 mg/mL to as high as 100 mg/mL when compared to amoxicillin. The compound 2‐Chloro‐N‐(4‐(1‐(2‐chloroacetyl)‐5‐(thiophen‐2‐yl)‐4,5‐dihydro‐1H‐pyrazol‐3‐yl) phenyl acetamide ( 4 a ) was found to be selective for gram‐positive with inhibition zone as 11 mm and 12 mm at 100 mg/mL for S.aureus and B.subtilis respectively [46] …”
Section: Chemistry Of Chalcone Derived Pyrazoline Derivativesmentioning
confidence: 99%